2014 IEEE Conference on Computer Vision and Pattern Recognition 2014
DOI: 10.1109/cvpr.2014.387
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesizability of Texture Examples

Abstract: Example-based texture synthesis (ETS) has been widely used to generate high quality textures of desired sizes from a small example. However, not all textures are equally well reproducible that way. We predict how synthesizable a particular texture is by ETS. We introduce a dataset (21, 302 textures) of which all images have been annotated in terms of their synthesizability. We design a set of texture features, such as 'textureness', homogeneity, repetitiveness, and irregularity, and train a predictor using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…From the results, we can see that our method provides excellent texture exemplars based on the given natural images; they always include the Fig. 7 Patches chosen by our method and that of Dai et al [18]. dominant textures in the input images.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…From the results, we can see that our method provides excellent texture exemplars based on the given natural images; they always include the Fig. 7 Patches chosen by our method and that of Dai et al [18]. dominant textures in the input images.…”
Section: Methodsmentioning
confidence: 78%
“…Firstly, we implemented the method proposed by Dai et al [18] and compared its results with those of our method, as shown in Fig. 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Set14 was proposed by Zeyde et al [ZEP12], while BD100 dataset contains the 100 testing images from the Berkeley Segmentation Dataset (BSDS300) [MFTM01]. In order to further evaluate the ability of all methods for texture recovery, a highly-desired property for image super-resolution, we created a new dataset by selecting 136 diverse texture images from the ETHSynthesizability dataset [DRV14]. The dataset is named SuperTex136.…”
Section: Datasetsmentioning
confidence: 99%
“…Over the past decades, tremendous investigations have been made in texture analysis, see e.g. [1][2][3][4][5][6][7], among which an active topic is developing texture models that can efficiently depict both the statistical and the geometrical aspects of textures and are robust to the variations of imaging condition as well.…”
Section: Introductionmentioning
confidence: 99%